Efforts of Teachers in Preserving Local Cultural Values Through a Workshop on Developing Simple Teaching Modules with Local Content in Tombulu Language at Walian Elementary School, INPRES 4/82 - Lengkong*, Jeffry S J; Rotty, Viktory N J; Usoh, Elni J; Lumapow, Harol R; Lantang, Dani (Riwayat: Educational Journal of History and Humanities, 2023)
The purpose of this research is to describe the efforts of teachers in preserving local cultural values through a Workshop on Developing Simple Teaching Modules with Local Content in Tombulu Language at Walian Elementary School, INPRES 4/82. This research adopts a qualitative research approach with a descriptive type. Data was collected through observation, interviews, and documentation. Data validity was ensured through source triangulation and technique triangulation. The results of the research indicate that the efforts of teachers in preserving local cultural values at Walian Elementary School, INPRES 4/82, are carried out through a Workshop on Developing Simple Teaching Modules with Local Content in Tombulu Language, which involves three stages of activities: Preparation stage, which involves preparing an Implementation Plan for the Workshop used as a guide in the upcoming activities. This includes preparing media, material, and competent speakers. Implementation stage, where on the first day, speakers provide an introduction, and participating teachers give feedback. The focus of the first day is on sharing and exchanging information related to Tombulu language proficiency. On the second day, teachers discuss and receive tasks to interview and collect data from parents or Tombulu language speakers. Additionally, teachers review written sources about Tombulu language. On the third day, teachers discuss and collect interview results. During this day, teachers, together with the speakers, formulate the structure of the teaching module. Evaluation stage, where evaluation is conducted collectively by teachers, the school principal, and speakers to determine whether the developed module is suitable for printing and use.